Aplikasi Olahan Limbah Ternak Terhadap Pertumbuhan Bayam Merah (Amaranthus tricolor L.) - Nurcaya, N; Suryani, Lili; Irfandi, Rizal; Syah, Uswah Trywulan; Ruslang, R (Journal Galung Tropika, 2021)
This study aims to determine the effect of the application of manure and bokashi fertilizer and their interaction on the growth of Red Spinach (A. Tricolor L.). This research was conducted in Atapage, Wajo Regency. The research design used was a completely randomized design (CRD) with 4 replications and consisted of 4 treatments, namely manure; bokashi fertilizer; manure + bokashi fertilizer; and without treatment. The research data were analyzed using variance and for the different tests, the Least Significant Difference Test was used at the 5% level. The results of the study statistically showed that the treatment given was significantly different from the observation parameters of plant height and number of leaves, the highest average was found in the treatment with bokashi fertilizer and the lowest was in the treatment without manure + bokashi fertilizer, while the root crown ratio parameter showed no significant difference.